Effect of Competence, Work Discipline and Work Stress on Employee Performance at PT Artha Centra Bangun Perkasa - Hendra Nazmi; Riyon Pamila; Ade Irma (Kusuma Negara Business School, 2022)
The purpose of the research carried out aims to see the analysis of the decline in performance at PT Artha Centra Bangun Perkasa down. HR has a very important function that aims to be able to achieve the goals the company PT Artha Centra Bangun Perkasa wants to achieve. So human resources must be more efficient and professional in dealing with problems and always take an existing opportunity. Apparently in this company, PT Artha Centra Bangun Perkasa really has problems with competence, discipline and work stress. Competence is not very good because the company does not place employee positions according to their education and abilities so that many employees do not understand or do not know the position they are currently occupying. Not only that, but the company’s employee discipline also there is not good. Many employees lack discipline in terms of attendance, and many are late because the company does not punish employees who do not comply with the rules so that employees dare to be undisciplined. Meanwhile, the company has to deal with work stress. Actually there are many companies that experience work stress, but there are some work stress that can be handled by the company. However, the company PT Artha Centra Bangun Perkasa is not able to cope with excessive employee work stress because most of the employees say that many jobs have short targets so that they become stressed in doing their work. Validation test is used with a population of 66 people and 30 people from companies that have similar industries. The method used is quantitative, using interviews, distributing questionnaires, and studying documentation. Multiple linear regression, coefficient of determination and simultaneous testing will be used in the analysis method. (Test – F) Fcount (23.681) > Ftable (2.75) and partially (Test – t) t-count competence |2.786| > ttable |1.99|, disciplined t-test |3.579| > ttable |1.99|, and stress t-test |-5,177| > ttable |-1.99|. It can be concluded that competence, discipline and work stress simultaneously and partially have a positive effect on employee performance.